Citizen science data to improve rainfall-runoff model performance in urbanizing Akaki Catchment, Awash Basin, Ethiopia - Mengistie, G. K.; Haile, Alemseged Tamiru; O'Donnell, G.; Negash, E. D.; Bekele, Tilaye Worku; Tedla, H. Z. (Elsevier, 2024)
Study region: Akaki is a headwater catchment of the Awash River Basin in Ethiopia and hosts Addis Ababa. The catchment remains ungauged despite providing diverse ecosystem services.